2018
DOI: 10.1002/hbm.24374
|View full text |Cite
|
Sign up to set email alerts
|

Altered structural and functional brain network overall organization predict human intertemporal decision‐making

Abstract: Intertemporal decision‐making is naturally ubiquitous to us: individuals always make a decision with different consequences occurring at different moments. These choices are invariably involved in life‐changing outcomes regarding marriage, education, fertility, long‐term well‐being, and even public policy. Previous studies have clearly uncovered the neurobiological mechanism of the intertemporal decision in the schemes of regional location or sub‐network. However, it still remains unclear how to characterize i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 175 publications
(400 reference statements)
1
22
0
Order By: Relevance
“…Furthermore, resting state fMRI studies have revealed interesting baseline patterns of activation (i.e., resting state networks), and ushered in an age of network science in brain research. With the rise in resting state fMRI research, predicting resting state fMRI functional connectivity from diffusion tensor imaging (DTI) structural connectivity has been an important recent endeavor for researchers, and the use of graph theory analyses of structural networks have been integral to these investigations (e.g., Honey, Thivierge, & Sporns, 2010;Goñi et al, 2014;Bettinardi et al, 2017;Zhang et al, 2019;Chen, Hu, Chen, & Feng , 2019). Furthermore, there has been recent interest in predicting taskbased fMRI activation from DTI structural connectivity (Osher et al, 2016;.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, resting state fMRI studies have revealed interesting baseline patterns of activation (i.e., resting state networks), and ushered in an age of network science in brain research. With the rise in resting state fMRI research, predicting resting state fMRI functional connectivity from diffusion tensor imaging (DTI) structural connectivity has been an important recent endeavor for researchers, and the use of graph theory analyses of structural networks have been integral to these investigations (e.g., Honey, Thivierge, & Sporns, 2010;Goñi et al, 2014;Bettinardi et al, 2017;Zhang et al, 2019;Chen, Hu, Chen, & Feng , 2019). Furthermore, there has been recent interest in predicting taskbased fMRI activation from DTI structural connectivity (Osher et al, 2016;.…”
Section: Introductionmentioning
confidence: 99%
“…These results are understandable since the neural structure of C. elegans was not optimised to solve the MNIST problem. Neurobiological research postulated that a specialized structure is always coupled with a certain function 2 , 3 . However, the structure needs to be changed only slightly so that it can solve this synthetic task more effectively, as evident in comparison with the C. elegans G ( n , p ) reference variant (not significant cases are shown in Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Going far beyond the obvious macroscopic structure of the brain, which hardly differs between human individuals, various authors postulated a coupling of structure and function 1 3 . Neurons, hubs, or in graph theory called nodes, with similar connection patterns often show similar functionality 4 , 5 .…”
Section: Introductionmentioning
confidence: 99%
“…The human brain serves as a highly complex and integrated network system. The graphtheoretical analysis of this complex network has resulted in a potent mathematical tool to quantify the collection of the comprehensive topological dynamics in these human structural connectomes (27). Considering the light of corresponding relationship between the function and structure of our brain (26), the structural foundation of the altruism changes that occur in older people is another question we want to investigate.…”
Section: Introductionmentioning
confidence: 99%